2014
DOI: 10.1111/apt.12695
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: Lactobacillus GG modulates gut microbiome, metabolome and endotoxemia in patients with cirrhosis

Abstract: Summary Background Safety of individual probiotic strains approved under Investigational New Drug (IND) policies in cirrhosis with minimal hepatic encephalopathy (MHE) is not clear. Aim The primary aim of this phase I study was to evaluate the safety, tolerability of probiotic Lactobacillus GG (LGG) compared to placebo while secondary ones were to explore its mechanism of action using cognitive, microbiome, metabolome and endotoxin analysis in MHE patients. Methods Cirrhotic patients with MHE patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
203
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(210 citation statements)
references
References 41 publications
4
203
2
1
Order By: Relevance
“…Being a safety study, this was not powered to detect cognitive changes, which were not observed between groups. Similar to the rifaximin MHE trial, however, there were significant changes in functionality related to pathways of amino-acid, vitamin, and bile acid metabolism in the LGG compared to the placebo group 43 ). Therefore in addition to just the microbiota composition, functional alterations of microbiota are important to analyze.…”
Section: Mhe Therapymentioning
confidence: 86%
“…Being a safety study, this was not powered to detect cognitive changes, which were not observed between groups. Similar to the rifaximin MHE trial, however, there were significant changes in functionality related to pathways of amino-acid, vitamin, and bile acid metabolism in the LGG compared to the placebo group 43 ). Therefore in addition to just the microbiota composition, functional alterations of microbiota are important to analyze.…”
Section: Mhe Therapymentioning
confidence: 86%
“…Probiotic administration has been shown to limit dysbiosis in many disease states, including colitis models, and to restore a normal microbiota composition more quickly than with placebo (289)(290)(291). Patients with minimal hepatic encephalopathy secondary to cirrhosis who were treated with LGG showed significantly increased prevalences of Lachnospiraceae and Clostridia cluster XIV and decreased prevalences of Enterobacteriaceae and Porphyromonadaceae relative to placebo-treated controls (292).…”
Section: Protective Mechanisms Of Probiotics Against Ulcerative Colitismentioning
confidence: 99%
“…It is thus of particular interest that probiotics such as LGG and S. boulardii have been found in some animal models to decrease the levels of Enterobacteriaceae and Porphyromonadaceae, which are increased in active UC (292). The ability of these and other probiotics to speed the restoration of the microbiota following antibiotic treatment and to promote the activity of butyrate-producing bacteria may also help prevent insults that lead to active UC.…”
Section: Summary Of Probiotic Mechanisms Of Action In Ulcerative Colimentioning
confidence: 99%
“…Although no proven statistical benefit over lactulose, probiotics had a better tolerated side-effect profile (Bajaj et al 2014a). Meta-analyses of the use of probiotics with the aim of favorably altering enteric flora towards reducing bacterial ammonia production have however shown conflicting results; one indicated an improvement in covert HE and secondary prevention of overt HE (Xu et al 2014), however another has shown no statistically significant benefit on clinical (McGee et al 2011).…”
Section: Therapeutic Strategies Targeting the Gut-liver-brain Axismentioning
confidence: 99%